WGS for surveillance of antimicrobial resistance: a pilot study to detect the prevalence and mechanism of resistance to azithromycin in a UK population of non-typhoidal Salmonella. (1st September 2016) - Nair, Satheesh; Ashton, Philip; Doumith, Michel; Connell, Steve; Painset, Anais; Mwaigwisya, Solomon; Langridge, Gemma; de Pinna, Elizabeth; Godbole, Gauri; Day, Martin
Abstract : This study showed that whole-genome sequencing was effective in screening large numbers of isolates of non-typhoidal Salmonella spp. from the UK for resistance determinants to azithromycin which were confirmed by EUCAST susceptibility testing. Abstract : Objectives: WGS and phenotypic methods were used to determine the prevalence of azithromycin resistance in Salmonella enterica isolates from the UK and to identify the underlying mechanisms of resistance. Methods: WGS by Illumina HiSeq was carried out on 683 Salmonella spp. isolates. Known genes associated with azithromycin resistance were detected by WGS using a mapping-based approach. Macrolide resistance determinants were identified and the genomic context of these elements was assessed by various bioinformatics tools. Susceptibility testing was in accordance with EUCAST methodology (MIC ≤16 mg/L). Results: Fifteen isolates of non-typhoidal Salmonella enterica belonging to serovars Salmonella Blockley, Salmonella Typhimurium, Salmonella Thompson, Salmonella Ridge and Salmonella Kentucky showed resistance or decreased susceptibility to azithromycin (from 6 to >16 mg/L) due to the presence of macrolide resistance genes mphA, mphB or mefB . These genes were either plasmid or chromosomally mediated. Azithromycin-resistant Salmonella Blockley isolates harboured a macrolide inactivation gene cluster, mphA - mrx - mphr(A), within a novel Salmonella azithromycin resistance genomic island (SARGI) determined by MinION sequencing. This is the first known chromosomally mediated mph A gene cluster described in salmonellae. Phylogenetic analysis and epidemiological information showed that mphA Salmonella Blockley isolates were not derived from a single epidemiologically related event. The azithromycin MICs of the 15 Salmonella spp. isolates showed that the presence of the mphA gene was associated with MIC ≥16 mg/L, while the presence of mefB or mphB was not. Conclusions: Azithromycin resistance due to acquisition of known macrolide resistance genes was seen in four different Salmonella serovars and can be either plasmid-encoded or chromosomally encoded.